Hamstring muscle injuries in athletics - Iatropoulos, S. A.; Wheeler, P. C. (The Physician and Sportsmedicine, 2024)
Hamstring muscle injuries (HMI) are a common and recurrent issue in the sport of athletics, particularly in sprinting and jumping disciplines. This review summarizes the latest literature on hamstring muscle injuries in athletics from a clinical perspective. The considerable heterogeneity in injury definitions and reporting methodologies among studies still needs to be addressed for greater clarity. Expert teams have recently developed evidence-based muscle injury classification systems whose application could guide clinical decision-making; however, no system has been adopted universally in clinical practice, yet.